Stratification of education for rural-urban migrant children: New trends of population control policy for China's super large-sized cities - Liu, Ting; S. Laura, Ronald (IJRDO- Journal of Educational Research, 2018)
This paper provides a contextualized interpretation of recent policy developments governing China's largest size cities and evaluates its impact upon the status of migrant children’s education in China. By teasing out its ramifications for educational equity, this paper reveals previously neglected but integral facets of the recent  population control policy pertaining to China's largest size cities. Our aim will be to show that this most recent policy has unwittingly brought many aspects of change to the character of migrant children’s education without sufficient critical reflection. This new population control policy has gradually infiltrated the very institutional structures and contexts of geographic isolation which circumscribe the opportunities which migrant children require to gain access and equitable treatment. Constructive analysis and exposure of the newly created problems arising from the policy will be initiated to galvanise alternatives and more empathetic options for the development of a more efficacious pathway to future directions of policy reform. It is to be hoped that the information provided will serve to advance governmental and institutional understanding of the subtleties of inequity that have emerged from the current policy of Chinese urbanization, facets of which that have to date not been appropriately acknowledged.